Penerapan Attention, Interest, Desire, Action (AIDA) Terhadap Komunikasi Pemasaran Kerajinan Tangan - Nia Kania Kurniawati; Nurprapti Wahyu Widyastuti; Muhammad Ihsan Alifi; Maulia Pratiwi; Hairun Nisa; Ibnu Chalis Maulana (Jurnal Ilmiah Wahana Pendidikan, 2022)
Tegal Village, Keragilan District, has many programs on farmer groups, women's dharma, handicrafts and others. This research uses a qualitative method by referring to AIDA is Attention: the shortcomings of the marketing aspect, this is what is found in handicraft products there is no special message or brand owned; Interest: has had a better point for the role of the village head who often encourages his community to participate in competitions either held by the government or companies; Desire: residents have the disadvantage of letting an exhibition boutique guard or a keeper selling goods just sell without understanding the concept of marketing communication, then what is the action aspect: residents do not understand how a buyer's habits can influence in determining the decision to buy the product or not. Suggestions in this study the need for some actions tailored to AIDA-based marketing communications